Effects of contract farming scheme on cassava production enterprise in Oyo State, Nigeria (2011)
There are indications that the domestic demand for cassava particularly as staple food may in no time outweigh that of the industrial sector, except contract and non-contract farming entrepreneurs operate within the framework of sustainable agriculture. The study thus examines the effects of contract farming scheme on cassava production in Oyo State, Nigeria. Multistage sampling technique was used. Oyo and Ibadan/Ibarapa zones were randomly selected from the four Agricultural Development Projects (ADPs) in Oyo State. From the 307 registered farmers under the contract farming arrangement in the selected zones, 20% (62) were randomly selected, while equal number were selected from the list of their non-contract counterparts in two of the four agricultural zones of the state. Data were subjected to descriptive and inferential statistics. Average farm size was 14.56 ± 3.43 and 2.14 ± 0.43 acres for Contract and non-contract farmers respectively with respective average output of 6 and 5.4 tonnes per acre. Majority financed the farm through loan as average distance from home to farm is 5.88km. Hired labour was prominent for farm operations and land for farming is through the community. Contract and non-contract farmers differed significantly in their level of production enterprise (t=19.219, p=0.000). Promotion of contract farming through a well laid out agricultural extension outreach will ensure constant and consistent growth in the agricultural sector and consequently alleviate poverty among rural household in Oyo State.